Fiber treatment impact on the thermal behavior of biomass/palm-fibers polylactic-acid hybrid biocomposites - Abdelaziz Lekrine; Ahmed Belaadi; Isma Dembri; Mohammad Jawaid; Ahmad Safwan Ismail; Djamel Ghernaout (Elsevier, 2025)
The purpose of this investigation was to develop 100 % natural biocomposites from biopolymers such as polylactic acid (PLA) based on treated fibers and biochar (B) derived from the Washingtonia filifera (WF) plant. The dynamic mechanical characteristics, coefficient of thermal expansion, and thermal stability (TS) of biocomposites were studied using dynamic mechanical and thermomechanical analyses. Increasing the fiber treatment period caused the melting temperature of the biocomposites to decrease. The PLA-BWF72 composite demonstrated better TS compared to the others. Compared to untreated hybrid biocomposites, these composites exhibit enhanced TS and resistance following treatment with sodium bicarbonate. The dynamic mechanical analysis revealed that PLA-BWF72 hybrid biocomposites (2621.987 MPa) had a significantly higher storage modulus (SM) than the biocomposites produced. However, PLA-BWF24 hybrid biocomposites showed the lowest SM (2299.174 MPa), indicating a low level of stiffness. Cole-Cole plots of the hybrid biocomposites developed revealed the presence of imperfect semicircles, indicating their heterogeneity.